1996
DOI: 10.1002/pc.10687
|View full text |Cite
|
Sign up to set email alerts
|

Fiber/Matrix mechanical interaction in carbon fiber/bismaleimide model composites

Abstract: The fiber/matrix interaction of high modulus (M40) and intermediate modulus (T800) carbon fibers with a bismaleimide resin has been studied by means of three micromechanical techniques involving a single fiber, namely, fragmentation, Raman spectroscopy, and pullout. A number of chemical treatments aimed at improving the fiber/matrix stress transfer at elevated temperature were tested. The stress transfer proved to be reduced by the temperature in the same way for all interfacial conditions. The limitations to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The weak interface can be regarded as a degraded interface, such as often results from ageing. The magnitude of glass fiber–epoxy interface strength was reported to be 10–100 MPa .…”
Section: Finite Element Analysismentioning
confidence: 99%
“…The weak interface can be regarded as a degraded interface, such as often results from ageing. The magnitude of glass fiber–epoxy interface strength was reported to be 10–100 MPa .…”
Section: Finite Element Analysismentioning
confidence: 99%
“…Single fiber fragmentation test (SFFT) is a widespread method to evaluate IFSS as demonstrated by several researchers . The micromechanical interfacial properties play a significant role to provide better strength of resulting hybrid composites such as CNT‐coated CF/Epoxy (CNT‐CF/Epoxy) compared to the neat‐CF reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies showed that adding carbon fiber into the concrete could improve effectively the strength and elastic modulus of the concrete [1][2][3]. The mechanical property of carbon fiber reinforced material mainly depended on the interfacial adhesion between the carbon fiber and the matrix [4,5], but the carbon fiber with smooth surface, low surface energy, resulted in the weak bonding strength between the carbon fiber and the matrix [6][7].When mixed the carbon fiber into the concrete via mechanical agitation, the fiber frequently winded with each other, which leaded to heterogeneous disperse in concrete; What's more, it was hard to exert the high strength and modulus of the carbon fibers in concrete due to the low bonding strength between the fiber and matrix resulted from the smooth surface of carbon fiber [8]. Therefore, the carbon fiber was necessary for surface treatment in practical application.…”
Section: Introductionmentioning
confidence: 99%